2016
DOI: 10.1177/0265813516647733
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of traffic noise distribution and influence factors in Chinese urban residential blocks

Abstract: To improve the acoustic environment of residential blocks, noise mapping is employed in this study to analyze traffic noise distribution and the influence factors of four types of residential blocks in China. The study shows that high-rise small blocks have the highest average noise level (L avg ) for ground and building facades, followed by small low-rise blocks while modern residential blocks yield the lowest value. An analysis of the standard deviation (STD) of spatial statistical noise level (L n ) shows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Levels of noise pollution in cities are influenced by the design of urban areas; urban density, urban morphology, street distribution, street environment, and urban land use are critical factors in noise pollution [ 26 ]. Cities with larger green spaces have, for instance, lower day-evening-night noise levels [ 26 , 27 , 28 ]. The day-evening-night levels of noise pollution also depend largely on commuting patterns [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Levels of noise pollution in cities are influenced by the design of urban areas; urban density, urban morphology, street distribution, street environment, and urban land use are critical factors in noise pollution [ 26 ]. Cities with larger green spaces have, for instance, lower day-evening-night noise levels [ 26 , 27 , 28 ]. The day-evening-night levels of noise pollution also depend largely on commuting patterns [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…As regards noise prediction, Zhou et al [ 34 ] generated noise maps for traffic noise in several types of buildings in China, and found that buildings with high-rise and small footprints have the highest noise levels in facades. Also, the parking lot area showed a negative association with the noise from building facades, while the floor space index shows a positive relationship.…”
Section: Building Material/shape/geometrymentioning
confidence: 99%
“…There are many urban development pattern indicators related to the sound environment (Badino et al, 2019;Zhou et al, 2016). Through literature reviews, we selected 75 indicators and categorised them into six groups: population, industrial structures, built-up areas, transport networks, commuting, and natural landscapes.…”
Section: Urban Development Pattern Indicatorsmentioning
confidence: 99%
“…A number of studies have examined the link between urban planning and environmental noise issues in terms of noise level and sound perception (Alberti, 1999;Zhou et al, 2016). From a noise level perspective, a comparative study by Wang and Kang (2011) demonstrated that there are significant differences in the spatial noise level distribution between highand low-density cities.…”
Section: Introductionmentioning
confidence: 99%